Drug-Induced Sleep Endoscopy Diagnostic and Therapeutic Applications. - de Vries, Nico (Thieme Medical Publishers, Incorporated, 2020)
The definitive resource on the innovative use of DISE for obstructive sleep apnea Obstructive sleep apnea is the most prevalent sleep-related breathing disorder, impacting an estimated 1.36 billion people worldwide. In the past, OSA was almost exclusively treated with Continuous Positive Airway Pressure (CPAP), however, dynamic assessment of upper airway obstruction with Drug-Induced Sleep Endoscopy (DISE) has been instrumental in developing efficacious alternatives. Drug-Induced Sleep Endoscopy: Diagnostic and Therapeutic Applications by Nico de Vries, Ottavio Piccin, Olivier Vanderveken, and.